Explaining Financial Crises: A Cyclical Approach - Marc Peter Radke (Peter Lang International Academic Publishers, 2005)
This book develops a new theoretical approach to the explanation of systemic financial crises in industrial and emerging market countries. In contrast to standard models, the present cyclical approach is consistent with the following three stylized facts. Firstly, systemic financial crises are a recurrent phenomenon generally accompanied by excessive boom-bust cycles. Secondly, the frequency of financial crisis cycles is very irregular. Thirdly, most financial crisis cycles are initiated by positive shocks to profit expectations which induce an unsustainable build-up of financial fragility driven by irrational exuberance. The present approach is based on a sophisticated balancesheet structure with many assets, as well as on an expectation formation scheme which combines the rational expectations hypothesis with Keynes' Beauty Contest Theory.
Keywords: 330